Language Shift Analysis of Javanese Language in South Tangerang - Poetri, Maharanny Setiawan; Ramadhina, Nabila Suci; Loka, Nur Widia; Tryana, Tryana; Sunarsi, Denok (STKIP Yapis Dompu, 2023)
This study aims to present language shift analysis of javanese language that is happened in South Tangerang. This study uses case study qualitative method that collects the data from 3 subjects about language shift that related to some theories and sources. The object of the study is language used of javanese language that provides subjects who have language shifting in their daily speaking. As a result, the research can claim that the Java language shift is influenced by bilingualism, migration, and economic, value, and attitude factor and the reason for the Java language shift into the Indonesian language is the status Indonesian language.